The Effectiveness of Borrower-Based Macroprudential Measures : A Quantitative Analysis for Slovakia - Juria, Pavol (IMF Working Papers; Working Paper ;, 2020)
We develop a semi-structural quantitative framework that combines micro and macroeconomic data to assess the effectiveness of combinations of borrower-based macroprudential measures in Slovakia. We expand on the integrated dynamic household balance sheet model of Gross and Poblacion (2017) by introducing an endogenous loan granting feature, in turn to quantify the potential (ex-ante) impact of macroprudential measures on resilience parameters, compared with a counterfactual no-policy scenario, under adverse macroeconomic conditions. We conclude that (1) borrower-based measures can noticeably improve household and bank resilience to macroeconomic downturns, in particular when multiple measures are applied; (2) those measures tend to complement each other, as the impact of individual instruments is transmitted via different channels; and (3) the resilience benefits are more sizeable if the measures effectively limit the accumulation of risks before an economic downturn occurs, suggesting that an early, preemptive implementation of borrower-based measures is indeed warranted.